METHODS OF DEVELOPMENT OF TRANSVERSAL COMPETENCIES OF FUTURE TEACHERS ON THE BASIS OF PROFESSIONAL REFLECTION (Web of Teachers: Inderscience Research, 2025)
The article is devoted to the methodology of developing transversal competencies of future teachers based on professional reflection. Transversal competencies are important for ensuring the successful activity of a teacher in the modern education system, and professional reflection is an effective tool for developing these competencies. This article analyzes the methodology of developing transversal competencies of future teachers based on professional reflection and defines the most effective methods of teaching.